Seven years' street preaching in San Francisco, California; embracing incidents, triumphant death scenes, etc. - Taylor, William, 1821-1902.; Strickland, W. P. (William Peter), 1809-1884. (New York, The author, 1857)
William Taylor (1821-1902) was a Methodist minister specializing in "street preaching" in Baltimore and Washington, D.C., when the Methodist church sent him to California as a missionary evangelist in 1849. He remained in the West for seven years, going on to become one of the church's most tireless worldwide evangelists. He later conducted crusades in Canada, Britain, Australia, New Zealand, South America, and South Africa. In 1884 he was named Missionary Bishop for Africa and he focused his energies on missionary activities on that continent. Taylor spent his last years in California, the site of his first mission. Seven years' street preaching in San Francisco (1857) offers Taylor's memoirs of his career in the West, concentrating on open-air evangelism in general and experiences on the street corners of San Francisco and Sacramento and in camp-meetings in the mine fields, 1849-1856. The book focuses on the nature of the sinners who repented at Taylor's words: drunkards, gamblers, seamen; and on the moral and political depravity of San Francisco that culminated in the creation of the Vigilance Committee. For a second installment of Taylor's memoirs, see California life illustrated (1858).
"Sixth thousand."
Also available in digital form on the Library of Congress Web site.
Also available in digital form on the Internet Archive Web site.
Keywords: San Francisco (Calif.); Evangelistic work; Ethnic groups -- California; Law -- Political aspects -- California; Mines and mineral resources -- California